2007
DOI: 10.2139/ssrn.1097111
|View full text |Cite
|
Sign up to set email alerts
|

Studying Microscopic Peer-to-Peer Communication Patterns

Abstract: This paper describes first results of an ongoing research effort using real time data collected by social badges to correlate temporal changes in social interaction patterns with performance of individual actors and groups. Towards that goal we analyzed social interaction among a team of employees at a bank in Germany, and developed a set of interventions for more efficient collaboration. In particular, we were able to identify typical meeting patterns, and to distinguish between creative and high-executing kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…This article also points to potential for research and real world deployment above and beyond these questions: the approach can also be used to identify weaknesses in enterprise networks and as a decision making tool in the process of group reorganization (see Gloor et al 2007;Putzke et al 2008). Organizational charts often fail to ref lect the actual group structures within the enterprise, as occurring due to unplanned, informal communications.…”
Section: Open Research Questions and Potentialsmentioning
confidence: 99%
“…This article also points to potential for research and real world deployment above and beyond these questions: the approach can also be used to identify weaknesses in enterprise networks and as a decision making tool in the process of group reorganization (see Gloor et al 2007;Putzke et al 2008). Organizational charts often fail to ref lect the actual group structures within the enterprise, as occurring due to unplanned, informal communications.…”
Section: Open Research Questions and Potentialsmentioning
confidence: 99%
“…Weblinks and blogs can be accessed via Google's blogsearch and Microsoft's live search API. Data gathered with Social Badges can also be loaded into Condor [29]. Not natively supported data sources can be loaded into Condor via flat files or by parsing the data directly into a MySQL database.…”
Section: Group-average Agglomerative Clusteringmentioning
confidence: 99%
“…Wu used F2F networks and proximity data to explain information workers' productivity and found a cohesive network topology is associated with higher productivity [13]. Gloor [14] also used F2F network data in a bank, comparing them with email network data, and found that temporal oscillation in a particular F2F network parameter, i.e., betweenness centrality, is a good indicator representing the creativity of a group.…”
Section: A Socially Aware Systemsmentioning
confidence: 99%